Comparing the Efficacy of Two Triple-Wash Procedures With Sodium Hypochlorite, a Lactic–Citric Acid Blend, and a Mix of Peroxyacetic Acid and Hydrogen Peroxide to Inactivate Salmonella, Listeria monocytogenes, and Surrogate Enterococcus faecium on Cucumbers and Tomatoes - Li, KaWang; Chiu, Yu-Chun; Jiang, Wentao; Jones, Lisa; Etienne, Xiaoli; Shen, Cangliang (Frontiers in Sustainable Food Systems, 2020)
This study was designed to evaluate two triple-wash procedures with commercial antimicrobials to inactivate foodborne pathogens and surrogate bacteria on cucumbers and tomatoes. Fresh, West Virginia locally grown cucumbers and tomatoes were dip-inoculated with Salmonella Typhimurium and Tennessee, Listeria monocytogenes (3-strain), and Enterococcus faecium. Produce was washed through two triple-wash steps (10 s each) including water dip, antimicrobial dip, and water dip (WAW), or water dip, water dip, and antimicrobial dip (WWA), followed by draining (2 min) on aluminum foil. A triple-water (WWW) process was also included as a water-only control. Tested treatments were (1) water; (2) sodium hypochlorite (SH, 100 ppm, pH 8.2); (3) acidified sodium hypochlorite (ASH, 100 ppm, pH 6.8 adjusted by citric acid); (4) lactic and citric acid blend (LCA, 2.5%); and (5) a H2O2-peroxyacetic acid mix [SaniDate-5.0 (SD) 0.0064, 0.25, and 0.50%]. Surviving bacteria were recovered on xylose lysine tergitol-4 (XLT-4, Salmonella), Modified Oxford (MOX, L. monocytogenes), and bile esculin agar (E. faecium). Data (two replicates, four samples/replicate) were analyzed using the mixed model procedure of SAS (P = 0.05). Counts of Salmonella, L. monocytogenes, and E. faecium on unwashed cucumbers and tomatoes were 5.42–6.23, 6.31–6.92, and 6.05 log colony-forming units (CFU)/produce, respectively. Triple-wash with water only reduced all three tested bacteria by 0.45–1.36 log CFU/fruit. Triple-wash by WWA with antimicrobials achieved additional reductions [least squares means (LsMeans)] of 0.38 log CFU/cucumber (Salmonella), 0.56 log CFU/cucumber (E. faecium), 1.48 log CFU/tomato (Salmonella), 1.09 log CFU/tomato (L. monocytogenes), and 0.71 log CFU/tomato more than the WAW procedure. Applying SD-0.25 and SD-0.50% solutions in triple-washing cucumbers and tomatoes resulted in reductions (P > 0.05) similar to ASH and greater reductions (P < 0.05) than SH and LCA. E. faecium was less susceptible (P < 0.05) or there was no difference (P > 0.05) in comparison with Salmonella in most cases, except for tomatoes treated with WWA. The results of this study indicate that SD could be used as an alternative antimicrobial agent for chlorine water in triple-wash processing at local small produce plants. Future pilot plant validation studies and cost-effectiveness analyses are needed for applying SD solutions in triple-wash by WV local small produce growers.